Raman and UV-visible spectrophotometer studies of hydrogenated amorphous carbon thin films - A. B., Suriani (American Institute of Physics, 2009)
Hydrogenated amorphous carbon (a-C:H) thin films were prepared using a direct-current plasma enhanced chemical vapor deposition (DC-PECVD) over a various range of DC power (w) in range of 0.2989-0.4218 W. Changes in the film properties due to DC-power were systematically studied by Raman spectrometer and UV-Vis spectrophotometer. Based on the results, the films studied in the present research are found to consist of sp2 clusters of which their size increases with increasing power during the deposition, resulting in lower hydrogen, sp3 content and optical band gap. The experimental results revealed that a-C:H properties are highly dependent on DC-power.